Developing a Pilot Case and Modelling the Development of a Large European CO2 Transport Infrastructure -The GATEWAY H2020 Project. (July 2017) - Jakobsen, J.; Bysveen, M.; Vågenes, E.; Eickhoff, Ch.; Mikunda, T.; Neele, F.; Brunner, L.; Heffron, R.; Schumann, D.; Downes, L.; Hanstock, D.
Abstract: The H2020 GATEWAY project aims to develop a comprehensive model Pilot Case which, intentionally, will pave the ground for CCS deployment in Europe. It will result from the assessment of, technical, commercial, judicial and societal issues related to a future CO2 transport infrastructure. The Pilot Case derived on this basis, will emphasize a gateway for CO2 transport in the North Sea Basin. Four potential pilot cases have been evaluated through a combination of techno-economic modelling of the individual cases and evaluation against more qualitative criteria. The chosen Pilot Case, Rotterdam Nucleus, will be refined and developed during the remaining period of the GATEWAY project. To maximise impact, the GATEWAY project adapts its work to lay the foundation for a future application to a European 'Project of Common Interest' (PCI). Continuous dialogue with the most relevant stakeholders is an important part of GATEWAY, as a Coordination and Support Action (CSA) H2020 project.